Efektivitas Metode Pengajaran Ilmu Tajwid Berbasis Multimedia Di Kalangan Mahasiswa - Mahmudi; Ramadhan, Muhammad; Rahmah, Husni; Maulana, Mizan; Mahendra, Idha (Yayasan Cendekia Gagayunan Indonesia, 2024)
This study aims to evaluate the effectiveness of multimedia-based teaching methods for Tajwid compared to traditional methods among university students. The research employed a quasi-experimental method with a pre-test and post-test design on 60 students from the Faculty of Islamic Studies at Universitas Islam Kebangsaan Indonesia (UNIKI). The sample was divided into two groups: a control group taught using traditional methods and an experimental group using multimedia-based methods. The results showed that the experimental group experienced an average score increase of 21.0 points, higher than the control group's 7.6 points (p-value < 0.05). Moreover, the multimedia method produced more consistent learning outcomes and higher student motivation due to its interactive learning elements. Challenges included limited devices, internet connectivity issues, and inadequate infrastructure. Thus, multimedia methods proved to be effective and innovative in improving Tajwid understanding, though they require adequate technological support.